Transformasi Elemen Rancang Bangun Tradisional dalam Tampilan Arsitektur Bangunan Kekinian - Maharani, Sylvia Agustine; Suartika, Gusti Ayu Made; Saputra, Kadek Edi (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 8 No 1 (2021): April 2021DO - 10.24843/JRS.2021.v08.i01.p06, 2021)
It is undeniable to express that architectural designs have a defining role in developing an identity, impression, and finally sense of a place. Traditional architecture which grows and develops along with the course of culture, natural conditions, geography, topography, and the social system, has characterized the existence of vernacular architecture of certain localities. The idea of embracing traditional architectural principles and forms into the current design of a built form has always been a real challenge. This encounter is even intensified when design in architecture is understood as a process of addressing needs, ideas, inspiration, conformance to a set of guidelines, as well as an embedded message an architect would like to convey through her/his design. This article discusses the approaches and efforts made by Grounds Kent Arsitek Indonesia (GKAI) in embracing traditional Balinese architecture in designing The Alantara Resort Sanur. This is a study that applies a qualitative approach, implementing interviews and in-depth design observations as its methods in data collection. By focusing on the building style, the results of this study show that there was a great deal of re-interpretation process of Balinese traditional architecture taking place, including 1) adaptation in the application of the Tri Angga concept; 2) domination in the use of local building materials; 3) adjustment in techniques as to how traditional building decorative elements are produced and used; 4) modification in the spatial hierarchy of certain structures; and 5) simplification in form of ornaments and decorative elements in use.  Keywords : traditional architecture; the architecture of the current building; building style   Abstrak Tidak bisa dipungkiri jika karya arsitektur memiliki peran penting di dalam membangun identitas, rasa dan kesan dari sebuah tempat - sense of place. Disini peran arsitektur tradisional yang tumbuh dan berkembang seiring perjalanan budaya, kondisi alam, geografi, tofografi, beserta sistem sosial kemasyarakatan memberi ciri pada keberadaan arsitektur vernacular. Menjadi tantangan bagi para arsitek untuk mengakomodasi wujud tradisi rancang bangun ini ke dalam desain, sebelum memunculkan karya desain yang merupakan peleburan antara ide, tradisi, dan kaidah-kaidah karya kekinian, serta pesan yang ingin disajiikan.  Artikel ini membicarakan tentang pendekatan serta upaya yang dilakukan oleh Grounds Kent Arsitek Indonesia dalam merangkul arsitektur tradisional Bali di dalam mendesain The Alantara Resort Sanur. Ini merupakan sebuah studi yang menerapkan pendekatan kualitatif, dengan metode interview dan observasi desain yang mendalam. Dengan berfokus pada tampilan bangunan, hasil penelitian menunjukan adanya reintrepetasi arsitektur tradisional yang mencakup 1) adaptasi penerapan konsep Tri Angga ; 2) dominasi dalam pemanfaatan bahan bangunan lokal; 3) pengolahan teknik pemanfaatan ragam hias tradisional pada badan bangunan; 4) penyesuasian skala hierarkhi vertical bangunan; dan 5) penyederhanaan pada ornamen dan ragam hias. Kata kunci: arsitektur tradisional; arsitektur bangunan masa kini; tampilan bangunan